Uso do comércio eletrónico na internacionalização das empresas portuguesas: estudos de caso - Meireles, Diana Cláudia Araújo (2021)
This study aims to analyse the use of e-commerce in the internationalisation process of Portuguese firms. In order to make the study relevant, in a first phase, a review of the existing literature on the subject was carried out and, later on, an empirical study was held, using a qualitative approach, more specifically, the case study method. As a first step, Portuguese companies that had an online platform and that sell their products/services to at least one foreign country were targeted as the most desired respondents. Then, in order to collect the primary data, semi-structured interviews were carried out with five companies that showed interest in participating on the study. The results showed that companies recognise that e-commerce provides benefits and advantages, and that the associated costs are lower compared to the costs of the traditional internationalisation process. E-commerce is considered a competitive advantage for companies in contrast to the competition. It is also confirmed that ecommerce boosts the internationalisation process of the interviewed firms. Another conclusion reached is that, mainly due to covid-19 and the social implications we are experiencing, firms consider increasingly important to use an online platform as a complement to traditional commerce or even as a unique sales channel.